Hubungan Kompetensi Sosial Guru Sejarah dengan Motivasi Belajar Siswa di SMKN 1 Payakumbuh - Febriani Rahayu Putri; Zafri Zafri (Jurnal Kronologi, 2021)
This study aims to find out how the relationship between the social competence of the history teacher and the student's motivation at SMK Negeri 1 Payakumbuh. The research method used by the author is a survey method with the type of Ex post facto research with a quantitative approach using a correlation study. The source of data in this study is primary data obtained from the results of the Questionnaire Answers that have been distributed to respondents. The results of this study indicate a positive correlation with a correlation coefficient of 0.525 > 0.05 with a sign of correlation and a moderate level of correlation. Based on the value of the coefficient of determination, the variable of History Teacher's social competence has an effect of 27.6% on students' learning motivation at SMKN 1 Payakumbuh.